Respuesta :
Answer:
(x+3)(x-9)
Step-by-step explanation:
x^2 -9x +3x -27 (add like terms) x^2+6x -27=0
Answer:
x = -9 or x = 3
Step-by-step explanation:
Given :
[tex]x^{2} +6x -27 = 0[/tex]
solving by factoring , we have to look for two factors that will be multiplied together to give [tex]-27x^{2}[/tex] and add to give [tex]6x[/tex].
The factors are :
[tex]9x[/tex] and [tex]-3x[/tex]
check:
[tex]9x[/tex] x[tex]-3x = -27x^{2}[/tex]
[tex]-3x + 9x = 6x[/tex]
The next thing is to replace [tex]6x[/tex] in the main equation with the two factors , the equation then becomes :
[tex]x^{2} +9x -3x - 27 = 0[/tex]
[tex]x(x+9)-3(x+9) = 0[/tex]
[tex](x+9)(x-3) = 0[/tex]
either [tex]x + 9 = 0[/tex] or [tex]x - 3 = 0[/tex]
Therefore :
[tex]x = -9[/tex] or [tex]x = 3[/tex]